Біографія філософа після «смерті автора»: випадок Фуко - Менжулін, В.І. (Українська біографістика, 2010)
The author analyses some focal aspects of the personality and heritage of the outstanding French philosopher of the XXth century, Michel Foucault. Special attention is devoted to the threats to the biographical research from the «death of the author» thesis proposed by the Foucault’s conceptual supporter Roland Barthes. It is made evident that in fact the thesis of the «death of the author» does not eliminate biographical aspect from the history of philosophy, but rather warns a biographer against such widespread error as a reductive, one-sided interpretation of the object of the research. Foucault made numerous theoretical assertions and practical steps in order to exclude the possibility of the biographical look at him. However, the interest to his personality has not been fading for decades. In this aspect his path is one of the striking examples of the fundamental paradox, which is immanent to the biographies of many true philosophers: they try to transcend the limits of their own subjectivity as much as they can, and because of that they obtain a rare privilege — the interest to their own subjectivity from the others.